Digital Platform; Real-time Monitoring and Performance Analysis of Waqf Funds - E. Mulya Syamsul; Muhammad Misbakul Munir; Rahmat Hidayat H (Prodi Manajemen Zakat dan Wakaf Fakultas Ekonomi dan Bisnis Islam, 2023)
This study discusses how digital platforms can provide real-time monitoring in analyzing the performance of waqf funds collected by Islamic or philanthropy institutions. The method used with a qualitative approach by trying to describe waqf institutions that have digitized waqf, the result of this study is that digitalization of waqf through digital platform services is excellent service and fast and accurate reporting so that public trust can continue to grow in response to money endowments, another opportunity is that the performance of Islamic philanthropy institutions, in this case, waqf is strongly challenged to continue to do Innovation in digital waqf literacy.